Relational bullying and disordered eating: Testing a moderated mediation model of the role of shame and self-compassion - Bellows, Lindsay A.; Couturier, Laura E.; Dunn, Leigh C.; Carter, Jacqueline C. (Frontiers in Psychology, 2023)
Objective: Experiences of relational bullying (RB) in adolescence are associated with the development of disordered eating. This association may be related to heightened shame resulting from perceived social inferiority, low social rank, and/or negative evaluation by others. Self-compassion may act as a protective factor against the influence of RB on shame and disordered eating. In the current study, we investigated whether shame mediated the relationship between recalled RB and current disordered eating in a sample of young adults. Then, using conditional process analysis, we examined whether the observed mediation was moderated by self-compassion. Method: Participants were 359 young adults (aged 17-25) who completed online self-report measures of recalled RB experiences and current disordered eating, shame, and self-compassion. Results: Experiences of RB were positively related to current shame and disordered eating, and negatively related to current self-compassion, with small-to-medium effect sizes. The association between RB and disordered eating was partially mediated by shame, and this mediation was moderated by self-compassion. Discussion: Our results suggest that young adults with lower self-compassion are more likely to demonstrate a relationship between recalled RB and disordered eating through the mechanism of shame. These findings have important implications for both anti-bullying awareness and eating disorder prevention programs.